Analisis Hasil Deteksi SARS-COV2 Menggunakan Rapid Tes Antigen di Laboratorium Mikrobiologi Klinik RSUD dr. Doris Sylvanus Palangkaraya: Analysis of SARS-COV2 Detection Using Antigen Rapid Tes in the Laboratory Clinical Microbiology RSUD dr. Doris Sylvanus Palangkaraya - Silvani Permatasari; Florence Felicia; Ni Putu W.S.W; Misbah Misbah; Arnino A; Dede Z. A; Yanuardi Ikhsan; Rini Fitri R; Chandra Chandra; Febrianto E. P (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The antigen rapid diagnostic test is used for screening COVID-19 patients and is easy to do anywhere and saves time. The sensitivity of various brands of rapid antigen test kits can vary, so medical personnel need to pay close attention to them. Testing for the SARS-CoV2 antigen kit needs to be done diagnostically. This study aims to determine the specificity, sensitivity, and accuracy of the Haelgen antigen rapid test through diagnostic tests. The study design was cross-sectional, with a total sample of 60 people who took swabs from the nasopharynx and oropharynx. The sample is placed in the viral transport medium (VTM). Samples were examined by RT-PCR and, at the same time, examined using an antigen rapid test. The results of the analysis were carried out by calculating the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of the SARS-Cov2 antigen test compared to standard RT-PCR using a diagnostic test formula. The most common characteristics of COVID-19 patients were female and 20–29 years old (28.3%). The results of the Haelgen rapid antigen diagnostic test showed a sensitivity of 92.31%, a specificity of 100%, a positive predictive value of 100%, a negative predictive value of 87.5%, and an accuracy of 95%. The sensitivity, specificity, and accuracy of the Haelgen rapid antigen are suitable for testing for COVID-19.